An assessment of subsoil organic carbon stocks in England and Wales. (23rd September 2013) - Gregory, A. S.; Kirk, G. J. D.; Keay, C. A.; Rawlins, B. G.; Wallace, P.; Whitmore, A. P.
Abstract It is estimated that half the soil carbon globally is in the subsoil, but data are scarce. We updated estimates of subsoil organic carbon (OC) in England and Wales made by Bradley et al. (2005) using soil and land‐use databases and compared the results with other published data. We estimated that the soils of England and Wales contained 1633, 1143 and 506 Tg of OC at 0–30, 30–100 and 100–150 cm depths, respectively. Thus, half of the soil OC was found below 30 cm depth. Peat soils accounted for the largest proportion, containing 44% of all the OC below 30 cm despite their small areal extent, followed by brown soils, surface‐water gley soils, ground‐water gley soils and podzolic soils. Peat soils had more than 25% of their profile OC per unit area in the 100–150 cm depth, whereas most other soils had <8% at this depth. The differences between soil types were consistent with differences in soil formation processes. Differences in depth distributions between land uses were small, but subsoil OC stocks in cultivated soils were generally smaller than in soils under grassland or other land uses. Data on subsoil OC stocks in the literature were scarce, but what there was broadly agreed with the findings of the above database exercise. There was little evidence by which to assess how subsoil OC stocks were changing over time.